2010
DOI: 10.1017/s136898001000193x
|View full text |Cite
|
Sign up to set email alerts
|

Nutrients and foods consumed by New Zealand children on schooldays and non-schooldays

Abstract: Objective: To describe and compare food and nutrient intakes in New Zealand (NZ) children on schooldays and non-schooldays. Design: Secondary analysis of cross-sectional data from the NZ 2002 Children's Nutrition Survey. Dietary intake was assessed using computer-assisted multi-pass 24 h dietary recalls in the home. Data were adjusted for survey weightings to be representative of the NZ population. The effect of day category on nutrient intake, and likelihood of consumption of food categories were determined u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
3
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 12 publications
(23 reference statements)
1
26
3
1
Order By: Relevance
“…Given the ages of the participants, however, these methods are most appropriate for obtaining more accurate recall. It has previously been demonstrated that children tend to have a higher intake of soft drinks and SSB on weekends and the actual intake may therefore be higher than the intake reported in the present study. Also, the different results obtained for fruit juice/cordial using yesterday's intake and usual intake in BAEW indicate that yesterday's intake may not reflect usual intake.…”
Section: Discussioncontrasting
confidence: 70%
“…Given the ages of the participants, however, these methods are most appropriate for obtaining more accurate recall. It has previously been demonstrated that children tend to have a higher intake of soft drinks and SSB on weekends and the actual intake may therefore be higher than the intake reported in the present study. Also, the different results obtained for fruit juice/cordial using yesterday's intake and usual intake in BAEW indicate that yesterday's intake may not reflect usual intake.…”
Section: Discussioncontrasting
confidence: 70%
“…The AI for Australian children from 2-16 years old ranges from 14 to 28 g. 39 We found the mean dietary fibre intakes for each age group were close to the current recommended AIs; however, the percentage of children meeting the AI decreased as age increased. Compared with the current population, previous studies in children have reported slightly lower fibre intakes: 10 g in 3-year-old Finnish children, 30 15-17 g in New Zealand 5-to 14-yearolds 40 and 13 g in adolescent boys from Canada. 41 Many of these children were also below current recommendations for fibre intake for their country.…”
Section: Discussioncontrasting
confidence: 67%
“…As food consumption patterns differ between school days and non-school days (day category) (9) , 24 h diet recalls were coded as to whether consumption fell by day category. Includes butter/margarine blends, reduced-fat spreads *A full list of original food groups and items can be found in Parnell et al (1) .…”
Section: Methodsmentioning
confidence: 99%